eBusiness adoption studies in Thailand - Jantavongso, Suttisak; Nuansomsri, Chuleekorn; Kasemsawasdi, Sumana; Anekritmongkol, Somboon; Sitthikraiwong, Saritkan (2016)
Electronic Business or eBusiness over the Internet enables businesses (whether large or small) to do more than buying or selling their products and services. eBusiness is now including all network based transactions, collaborations, and interactions with customers, suppliers, and business partners.Given the economic dominance of Western economies in fields such as eBusiness, a number of questions arise associated with the suitability of lessons learned in the West to eBusiness developments in Thailand.In particular, the authors have noted that most existing eBusiness adoptions are designed to cater for businesses in Western countries; and this raises the question of whether these adoptions are suited to businesses in Thailand.In this regard, the authors are of the opinion that a study explicitly on eBusiness is required to assist businesses in Thailand to adopt and engage in eBusiness successfully. The research findings provide the foundation for future research aimed at developing a framework to guide businesses in Thailand, to successfully implement the new generation of eBusiness activities, which include sCommerce (Social Commerce) and sBusiness (Social Business).